(untitled) (Research, Society and Development, 2025)
Bibliometrics has become a fundamental quantitative tool for mapping the research output of scholars, leading journals, academic institutions, and countries. The oral microbiota is a recently studied concept that plays an important role in the process of health and disease, especially concerning the aging process. The present study aimed to conduct a bibliometric review to analyze the evolution of publications on the terms of "oral microbiota" and "elderly population. The data was extracted from Scopus. Data on authors, countries, most cited journals, co-authorship between countries and authors, co-occurrence of keywords, co-occurrence of keywords based on the year of publication and co-citation of references were analyzed using the VOSviewer software. A total of 619 documents (1970–2024) were retrieved, with a significant rise in publications from 2018 and a peak in 2021. Ghannoum MA, the United States, and PLOS ONE were the most cited author, country, and journal, respectively. The most recurrent keywords included “oral microbiota” (n=173), “microbiota” (n=53), “oral microbiome” (n=51), “saliva” (n=45), and “periodontitis” (n=44). Findings highlight the increasing research interest in the relationship between oral microbiota and aging, particularly in oral health and diet, emphasizing its relevance in elderly care.